2020
DOI: 10.1111/ijpp.12601
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of pharmacy and non-pharmacy students towards mental illness in Nigeria: a comparative survey

Abstract: Objectives Globally, persons with mental illness are victims of stigma, even among healthcare professionals and trainees. However, in Nigeria, little is known about the attitudes of pharmacy students towards people with mental illness. Therefore, the objectives of this paper were to assess and compare the attitudes of pharmacy and non-pharmacy students towards mental illness and explore its associated demographic factors. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
1
6
0
1
Order By: Relevance
“…Two studies carried out in 2017, and 2018 [44, [45] had shown a negative attitude towards mental illness among young people in a secondary school and a University in Nigeria, respectively. Another study reported a positive attitude by Pharmacy students [46].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies carried out in 2017, and 2018 [44, [45] had shown a negative attitude towards mental illness among young people in a secondary school and a University in Nigeria, respectively. Another study reported a positive attitude by Pharmacy students [46].…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported the same discriminatory attitudes among all cadres of people, including healthcare workers and even clergymen. [11][12][13][14][15][16][17][18][19][20][21][22][23] There is the need for a shift from inpatient psychiatric mental health care towards a community-based care.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies 13 - 15 show that pharmacy students have negative attitudes toward people with mental health disorders. Assessing pharmacy students' attitudes toward people with mental health disorders is important as pharmacy students represent future pharmacists, and improving their attitudes through interventions implemented at this stage to address the negative attitudes, if any, may translate to better service delivery when they, in turn, become practicing pharmacists.…”
Section: Introductionmentioning
confidence: 95%
“… 19 Few studies among pharmacy students in Nigeria show negative attitudes and stigma. 15 , 20 The module on mental health disorders is taught in the final year of the BPharm degree program. The pharmacotherapy of schizophrenia is a major focus of this module, and case studies of patients with schizophrenia are discussed at the end of lectures.…”
Section: Introductionmentioning
confidence: 99%